2004
DOI: 10.1590/s1806-83242004000300011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the diameter on Cu-Al post retention

Abstract: ABSTRACT:This study compared the resistance to removal by traction of abraded cylindrical metal cast posts of Cu-Al (Goldent-LA). The posts had constant length (9 mm) and three different diameters (0.9, 1.3 and 1.7 mm), and were cemented with zinc phosphate cement. The crowns of 36 sound maxillary canines were sectioned, the roots were immersed in resin blocks and the root canals were endodontically treated. The teeth were divided into three groups to be prepared and standardized with the use of a parallelomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…22 Concerning the techniques available for radicular post cementation, several studies have attempted to explain the divergent results found in literature regarding the bond strength they provided. 2,5,9,12,14,21,24,25 Recently, Carvalho et al 4 (2004) and Alfredo et al 2 (2005) reported that the success in retention of cores and intracanal posts cemented with adhesive agents depend on a conjunction of factors including root canal preparation and operative procedures, specially the application method of the adhesive system and luting agent.…”
Section: Introductionmentioning
confidence: 99%
“…22 Concerning the techniques available for radicular post cementation, several studies have attempted to explain the divergent results found in literature regarding the bond strength they provided. 2,5,9,12,14,21,24,25 Recently, Carvalho et al 4 (2004) and Alfredo et al 2 (2005) reported that the success in retention of cores and intracanal posts cemented with adhesive agents depend on a conjunction of factors including root canal preparation and operative procedures, specially the application method of the adhesive system and luting agent.…”
Section: Introductionmentioning
confidence: 99%